A wave-like anastomosis, a new technique of anastomosis to prevent stricture after oesophageal atresia repair - Mohamed Oulad Saiad (Wolters Kluwer Medknow Publications, 2021)
Background: Anastomotic stricture still a frequent postoperative complication. Its development is multifactorial, nonetheless by improving some factors we can prevent the stricture. Anastomotic technique is among the factors that can be improved to prevent this complication. Aims and Objectives: Our aim is to report a new technique of anastomosis with a multiple plain suture, wave-like anastomosis and large low traction zone to prevent stricture after esophageal atresia repair. Furthermore this is a self-patient's anatomy dependant technique. Materials and Methods: A retrospective study reported forty nine esophageal atresia survivals without significant difference in weight and gap length. They were divided in two groups A and B with respectively eighteen and thirty one patients. The wave-like anastomosis technique is used in group A but in the group B an end to end anastomosis was used. Results: After a mean follow-up of 3 years no patient of the group A presented with anastomotic stricture and eight patients in the group B presented with stricture (p=0,046) so there was a significant difference between the two groups. Conclusion: This is a technique providing a multiple plain anastomosis, increasing the lumen in the anastomotic site and helping to prevent anastomotic stricture.